Early Childhood Education in the Mediterranean : Availability, Accessibility and Affordability of Services - Sollars, Valerie; Toran, Mehmet (Comparative Education and the Mediterranean Region, 2025)
The existing body of comparative studies on ECEC in the Mediterranean region has received little attention from the academic community. The chapters in this book make a significant contribution by providing prospective readers with a comprehensive overview of the current state of affairs in the region, highlighting the challenges faced by ECEC and stimulating further discourse and research on the future of the sector. In addition, the chapters in this volume represent a diverse and important collection, reflecting the unique characteristics of the respective countries. Contributors are: Bassel Akar, Anies Al-Hroub, Elina Antoniou, Sofia Avgitidou, Ebru Aydın, Nicoletta (Niki) Christodoulou, Rahime Cobanoglu, Thomas Cook, Fetiye Erbil, Abdelbasit Gadour, Mine Göl-Güven, Gülçin Gülmez, Thanaa Hashem, Reem Jawabreh, Pandelis Kiprianos, Mohamed Miliani, Soheil Salha, Valerie Sollars, Maura Striano, Habib Tiliouine, Nasser Tolba, Ziya Toprak, Mehmet Toran, Adrijana Višnjić-Jevtić, Ivana Visković and Farah El Zein.